Sympathetic Activation is Associated with Exercise Limitation in COPD. (2nd September 2016) - Haarmann, Helge; Folle, Jan; Nguyen, Xuan Phuc; Herrmann, Peter; Heusser, Karsten; Hasenfuß, Gerd; Andreas, Stefan; Raupach, Tobias
ABSTRACT: Exercise intolerance, skeletal muscle dysfunction, and reduced daily activity are central in COPD patients and closely related to quality of life and prognosis. Studies assessing muscle exercise have revealed an increase in sympathetic outflow as a link to muscle hypoperfusion and exercise limitation. Our primary hypothesis was that muscle sympathetic nerve activity (MSNA) correlates with exercise limitation in COPD. MSNA was evaluated at rest and during dynamic or static handgrip exercise. Additionally, we assessed heart rate, blood pressure, CO2 tension, oxygen saturation (SpO2), and breathing frequency. Ergospirometry was performed to evaluate exercise capacity. We assessed MSNA of 14 COPD patients and 8 controls. In patients, MSNA was negatively correlated with peak oxygen uptake (VO2 % pred) (r = −0.597; p = 0.040). During dynamic or static handgrip exercise, patients exhibited a significant increase in MSNA, which was not observed in the control group. The increase in MSNA during dynamic handgrip was highly negatively correlated with peak exercise capacity in Watts (w) and peak oxygen uptake (VO2/kg) (r = −0.853; p = 0.002 and r = −0.881; p = 0.002, respectively). Our study reveals an association between increased MSNA and limited exercise capacity in patients with COPD. Furthermore, we found an increased sympathetic response to moderate physical exercise (handgrip), which may contribute to exercise intolerance in COPD.